LENDING TO THE POOR: THE WORLD BANK IN URBAN DEVELOPMENT IN INDIA SANGHAMITRA NATH - Nath, Sanghamitra (European Scientific Journal, ESJ, 2015)
In India, the politics of development took the shape of the World Bank influenced housing policy for the urban poor. It was a recipient as well as an accomplice to the politics of development. Globalisation induced development brought opportunities and growth in metropolitan cities and towns, thereby, triggering large-scale urban migration. Since rapid urban migration surpassed rising demand for urban shelter, the government initially acted as the sole provider of subsidised housing for the urban poor. Due to multiple shortcomings, it withdrew from its role and became an enabler of World Bank’s housing policy for the urban poor. The World Bank’s attempt at urban development by lending to the urban poor for urban housing missed the point that the urban poor should be consulted for their views on their development. This paper uses a bottom-up approach to understand how the politics of development is countered by the subjects of development.